2007
DOI: 10.1021/ja067422e
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Structural Evolution of Calcium Carbonate Particles:  A Unifying Model of Copolymer-Mediated Crystallization

Abstract: Two double-hydrophilic block copolymers, each comprising a nonionic block and an anionic block comprising pendent aromatic sulfonate groups, were used as additives to modify the crystallization of CaCO3. Marked morphological changes in the CaCO3 particles were observed depending on the reaction conditions used. A poly(ethylene oxide)-b-poly(sodium 4-styrenesulfonate) diblock copolymer was particularly versatile in effecting a morphological change in calcite particles, and a continuous structural transition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
276
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 248 publications
(294 citation statements)
references
References 61 publications
14
276
0
2
Order By: Relevance
“…A continuous transition in building unit particle size to molecules on the one hand and of decreasing mutual order of the nanoparticle subunits on the other, places mesocrystals as structural intermediate between a classical single crystal composed of atoms/ions/molecules and a polycrystal without any mutual order between its nanoparticle subunits. 6) This intermediate structure of mesocrystals between single crystal and polycrystal was very recently also found for Ag mesocrystals. 7) Mesocrystals are usually not stable against crystallographic fusion of their nanoparticle subunits to a single crystal, if their nanoparticle subunits are in crystallographic register, since the subunits are aligned and the system can win a substantial amount of energy by elimination of these internal surfaces.…”
Section: Introductionsupporting
confidence: 64%
“…A continuous transition in building unit particle size to molecules on the one hand and of decreasing mutual order of the nanoparticle subunits on the other, places mesocrystals as structural intermediate between a classical single crystal composed of atoms/ions/molecules and a polycrystal without any mutual order between its nanoparticle subunits. 6) This intermediate structure of mesocrystals between single crystal and polycrystal was very recently also found for Ag mesocrystals. 7) Mesocrystals are usually not stable against crystallographic fusion of their nanoparticle subunits to a single crystal, if their nanoparticle subunits are in crystallographic register, since the subunits are aligned and the system can win a substantial amount of energy by elimination of these internal surfaces.…”
Section: Introductionsupporting
confidence: 64%
“…It is conceivable that this organic ring structure acts to nucleate aragonite into the highly oriented nano-crystals (~50 nm in size) that make up the meso-crystal (i.e. µm sized) nacre tablets (Wohlrab et al, 2005;Kulak et al, 2007). This adds support for a highly dynamic biomineralization process during which organic materials and carbonate precursor phases (likely amorphous) are delivered to the site of nacre tablet formation from the overlying mantle with a high degree of spatial control.…”
Section: Nacre Growth Mechanismmentioning
confidence: 99%
“…Wang et al 10 synthesized complex "flower type" vaterite superstructures in the presence of urea at high temperatures. Kulak et al 11 reported a variety of CaCO 3 particles of varying crystallinity in the presence of two double-hydrophilic block copolymers. Walsh et al 12 described a method for synthesizing hollow porous shells of crystalline aragonite that resemble the coccospheres of certain marine algae.…”
Section: Introductionmentioning
confidence: 99%